Multiple geophysical methods used to examine neotectonic structures in the western foothills of the Sierra de El Maitén (Argentina), North Patagonian Andes. Issue 3 (24th October 2015) - Klinger, Federico Lince; Orts, Darío; Gimenez, Mario; Folguera, Andrés; Martinez, Patricia
ABSTRACT: A high‐resolution geophysical study was carried out in a region of the retroarc of the Patagonian Andes located on the western slope of the Sierra de El Maitén. This structure is characterized by an imbricated west‐vergent fault system developed in the orogenic front area of the North Patagonian Andes that has uplifted. Oligocene volcanic rocks (Ventana Formation) affect Miocene to Quaternary sediments. Even though neotectonic fault scarps are affecting Quaternary deposits in the foothills of this range, no direct observation of slip in Quaternary strata was determined. The main objective of this study is to determine geometry of recognized neotectonic structures, characterizing them by variations in magnetic susceptibility, density, and p‐wave velocities. The combined application of different geophysical methods has allowed the characterization of the bedrock geometry and the determination of neotectonic displacements along faults. The potential field model and its integration with a seismic profile show the accurate geometry of this tectonic zone, which is crucial for seismogenic hazard analysis, in the area of northern Patagonia, a highly significant economic zone due to tourism with several towns (El Maitén, Esquel, and San Carlos de Bariloche) dispersed throughout the area of young tectonic activity.